Action learning: resources held in Manchester and Salford. (4th May 2022) - Pedler, Mike; Edmonstone, John; Chambers, Naomi; Mahon, Ann; Clark, Elaine; Baxter, Helen; Mitchell, Alexandra; Garlick, Victoria
ABSTRACT: This paper aims to make known the materials on action learning that are held in the uni- versities of Salford and Manchester, with the aim of bringing these unique resources to the attention of researchers and other interested parties. It is a joint effort between the Editorial Board members of the Journal, Action Learning: Research & Practice and staff at the two universities. Subsequently, we hope to publicise further resources available elsewhere. The paper begins with a brief history. Starting with Revans, his career and the early development of the action learning idea, it also records his long association with Manchester and some recent institutional history beginning with him donating his archives to the University of Salford. This is followed by introductions to the Revans Archive at Salford University and the action learning materials held at Alliance Manchester Business School (AMBS). Details of the two collections are in the latter part of the paper.